Pengembangan Aplikasi Ojek Online (BLOON) Berbasis Android Studi Kasus Provinsi Bengkulu - Hutagalung, Carli Apriansyah; Rizki, Sestri Novia (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Online motorcycle taxi services have become a trending topic as they are considered an innovative solution to enhance the efficiency of traditional motorcycle taxis. Many province in Bengkulu Regency face difficulties in finding reliable transportation services for delivery purposes due to the unavailability of online motorcycle taxi services like Gojek, Grab, or Maxim, which are common in larger cities. This research aims to design the Bengkulu Online Motorcycle Taxi (BLOON) application for Android using the Object-Oriented Analysis and Design (OOAD) methodology. OOAD is an analytical approach that evaluates requirements from the perspective of classes and objects within the problem's domain, surpassing traditional software architecture through the manipulation of system or subsystem objects. The Rapid Application Development (RAD) model is employed in this research. Through thorough analysis, design, testing, and implementation, the Bengkulu Online Motorcycle Taxi application demonstrates successful operation in line with the research objectives and plans. The application of the OOAD methodology proves effective in developing structured applications.